Consumer Trust in Unlabeled Halal Products on Brem from a Sharia Compliance Perspective - Hayu Alfian; Shinta Maharani; Ely Masykuroh (Journal of Economics, Law, and Humanities, 2026)
Background/Introduction: In Indonesia, halal certification functions as an important instrument for ensuring that products comply with sharia principles, particularly in a Muslim-majority society. In Madiun Regency, where the Muslim population is overwhelmingly dominant, Brem Suling Istimewa remains a widely consumed traditional product despite the absence of halal certification. This situation raises an important scholarly issue concerning the persistence of consumer trust in products without halal labels, even though sharia compliance is considered a significant aspect of Muslim consumption behavior. Research Objectives: This study aims to: (1) examine the level of consumer trust in Brem Suling Istimewa Madiun without halal certification; (2) analyze such trust from the perspective of sharia compliance; and (3) identify the strategies undertaken by producers to participate in the halal certification program. Methodology: This study employed a descriptive qualitative approach. The research involved producers and consumers selected purposively based on their relevance to the research problem. Data were collected through in-depth interviews, direct observation of the production process, and document analysis. Data were analyzed through data reduction, data display, and conclusion drawing. The validity of the findings was strengthened through source and method triangulation. Results: The findings indicate that consumer trust is shaped by three principal factors: consistent product quality, the producer’s reputation and long-standing relationship with retailers, and confidence in the traditional production process. Nevertheless, the absence of halal certification creates syubhat, particularly among consumers with a stronger orientation toward sharia compliance, mainly due to concerns regarding alcohol content resulting from fermentation. Producers have demonstrated commitment to halal certification through routine alcohol testing, the preparation of hygiene-related standard operating procedures, and cooperation with halal raw material suppliers. Unique Contribution: This study contributes to the literature on sharia economics by integrating consumer trust and sharia compliance perspectives in the context of traditional local fermented products. Conclusion: Halal certification is essential for strengthening Muslim consumer trust and ensuring product compliance with sharia principles. Recommendations: urther efforts are needed to provide mentoring for MSME producers in the certification process and to enhance public awareness of the importance of halal labeling.